Boarding School Program for Strengthening Qur’anic Knowledge and Character: Program Sekolah Berasrama untuk Memperkuat Pengetahuan dan Karakter Qur'ani - Arrasyidin, Arrasyidin; Azani, Mohammad Zakki (Halaqa: Islamic Education Journal, 2025)
Basically, education is a continuous process that aims to shape humans to have spiritual and intellectual values. Boarding schools play a crucial role in shaping character and morals according to religious teachings. This is reflected since its establishment, where the system combines the pesantren curriculum with the public school curriculum. The purpose of this study is to describe and find out the boarding school program in improving the knowledge of the Qur'an and character building at SMK At-Taqwa Miri Sragen. This research used descriptive qualitative method with case study approach. The population in this study were the principal, tahfidz teacher/character builder, boarding school manager, and 30 students of class XII of SMK At-Taqwa Muhammadiyah Miri. The research instruments used were interviews, observation, and documentation. The results showed that the implementation of boarding school activities carried out at SMK Muhammadiyah Miri Sragen is the inculcation of adab and morals in every academic and non-academic activity and encourages the improvement of Qur'anic knowledge with various activities such as memorizing Tahfidz, Tahsin, Tarjamah, Talaqqi. This study is based on the domain of religious value-based character education, which is specifically in the realm of value transformation in Islamic education, where Islamic spiritual and moral values are transformed into the concrete behavior of students through an educator approach. Highlights: Integrated Curriculum: Combines pesantren and public school education to nurture both spiritual and academic growth. Character Development Focus: Embeds adab and morals through daily academic and non-academic boarding school activities. Qur’anic Enrichment Programs: Emphasizes memorization (Tahfidz), pronunciation (Tahsin), translation (Tarjamah), and direct recitation (Talaqqi). Keywords: Boarding School Program, Qur'anic Knowledge, Character Education, Islamic Values